(untitled) (Research, Society and Development, 2020)
Discrimination sensory tests aim to identify if a difference between two similar stimuli is detected. In this study we compared the efficacy of Tetrads and Triangle tests in the difference detection between two samples of guarana soft drink, by means of the calculation of proportion of discriminators and thurstonian distance. Evaluated samples were produced by different syrup clarification methods (activated carbon and ionic exchange column). For each test 99 testers were used; Triangle test evaluated three samples, while Tetrad four samples, in complete randomized blocks. Only Tetrad test was able to detect significant difference between the samples (p<0.05), with a low proportion of discriminators and thurstonian distance inferior to perception limit, demonstrating that Tetrad test is more powerful and sensible than Triangle test.